2018
DOI: 10.1016/j.pmedr.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The fecal immunochemical test (fit): Selected aspects regarding its effectiveness for colorectal cancer screening in Quebec City

Abstract: Background and aimsFIT's value has been ascertained across Canada and worldwide, but still needs to be assessed within the province of Quebec. There also remains a gap between formal indications for FIT, and its actual use in clinical practice. This research aims to evaluate some aspects of FIT's effectiveness in our setting, and its application by prescribers.MethodsWe retrospectively identified and reviewed all the colonoscopies conducted for a positive FIT in 2014 at 2 hospitals located in Quebec City.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…30 While FIT is considered to have more clinical and analytical sensitivity over other tests in detecting occult blood, a marker for neoplasms, 31 how the prioritization of FIT patients impacted other colonoscopy-seeking patients has not been explored. FIT positive patients in Quebec may constitute a higher risk population than participants in other screening programs, 32 as the province has the highest positivity threshold across Canada (175ng/mL), 33 which may support their prioritization. Our study suggests that with finite colonoscopy resources, wait times for other indicated conditions may have been displaced by this reorganization.…”
Section: Discussionmentioning
confidence: 99%
“…30 While FIT is considered to have more clinical and analytical sensitivity over other tests in detecting occult blood, a marker for neoplasms, 31 how the prioritization of FIT patients impacted other colonoscopy-seeking patients has not been explored. FIT positive patients in Quebec may constitute a higher risk population than participants in other screening programs, 32 as the province has the highest positivity threshold across Canada (175ng/mL), 33 which may support their prioritization. Our study suggests that with finite colonoscopy resources, wait times for other indicated conditions may have been displaced by this reorganization.…”
Section: Discussionmentioning
confidence: 99%
“…To date, all approved immune checkpoint inhibitors (ICIs) are monoclonal antibodies that block cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), programmed cell death protein 1 (PD-1), or programmed death ligand 1 (PD-L1). These molecules serve as key inhibitors of T-cell activation and function ( 1 , 2 ). Since ipilimumab was approved by the FDA for metastatic melanoma in 2011, various ICIs have been introduced, Numerous studies have demonstrated the benefits of ICIs in non-small cell lung cancer ( 3 , 4 ), liver cancer ( 5 ), triple-negative breast cancer ( 6 ), gastroesophageal cancer ( 7 ), ovarian cancer ( 8 ) and other malignant tumors.…”
Section: Introductionmentioning
confidence: 99%